THE INFLUENCE OF SERVICE QUALITY, PRICE PERCEPTION, AND PRODUCT QUALITY FROM PT KERETA API INDONESIA (PERSERO) ON CUSTOMER SATISFACTION AT PT BUKIT ASAM, TBK - Saputra, Mohammad Reza; Widiyanti, Marlina; Shihab, Muchsin Saggaff; Maulana, Ahmad (International Journal of Social Service and Research, 2024)
This study examines the factors influencing customer satisfaction of PT Bukit Asam, Tbk regarding the services and products provided by PT Kereta Api Indonesia (Persero) for coal transportation. Customer satisfaction is analyzed based on three key factors: service quality, price perception, and product quality, specifically in transporting coal from the Tanjung Enim Mining Unit to Tarahan Port and Kertapati Pier, which accounted for 32,423,156 tons transported in 2023. The research findings indicate that all three factors—service quality, price perception, and product quality—have a positive and significant effect on customer satisfaction. The contribution of this research is twofold: it provides insights into the direct impact of these factors on corporate customer satisfaction and offers practical recommendations for PT Kereta Api Indonesia (Persero) to enhance its service performance, thereby improving its competitiveness in Indonesia's transportation and logistics sector. Future research could focus on additional factors, such as technological innovation and environmental sustainability, and investigate their influence on customer satisfaction across different industries or regions, offering broader insights into service quality improvement in the logistics industry.